Considerations on non-ketotic hyperglycinemia in 21st century - V. M. Studenikin (Лечащий Врач, 2022)
The paper is dedicated to non-ketotic hyperglycinemia and contemporary considerations on this metabolic disorder. Nonketotic hyperglycinemia is a rare, genetically heterogeneous disease (fermentopathy) caused by mutations that lead to disturbances in the metabolism of glycine and the accumulation of large amounts of the latter in organs, tissues and body fluids, which is accompanied by numerous disorders of the functions of the central nervous system and leads to severe developmental delay. The etiopathogenesis of nonketotic hyperglycinemia depends on the deficiency of one or another protein – P, T, H and L. These proteins are involved in the breakdown of glycine in the central nervous system, liver and kidneys, and with nonketotic hyperglycinemia there is a significant decrease in the activity of the glycine-cleaving system with metabolic disorders and utilization of glycine. The resulting accumulation of glycine in the body is manifested by the inhibitory effect of this amino acid on the structures of the spinal cord and brain stem, which simultaneously leads to excitation of cerebral neurons and damage to the central nervous system with the corresponding clinical manifestations of the disease. The article touches upon the epidemiological and genetic aspects of nonketotic hyperglycinemia, variants and subvariants of the disease with a description of the leading clinical symptoms of nonketotic hyperglycinemia. The possibilities of therapeutic approaches to non-ketotic hyperglycinemia are particularly examined. The basic principles and available methods for non-ketotic hyperglycinemia diagnostics are described along with proper differential diagnosis. Some of the listed methods of treatment for non-ketotic hyperglycinemia (exchange blood transfusions, folate, strychnine) are of purely historical interest, while the use of reductors of blood plasma glycine content (sodium benzoate) and NMDA-receptor site antagonists (dextromethorphan, ketamine) have practical significance. Some peculiarities of antiepileptic drugs’ use in non-ketotic hyperglycinemia, and main alternative therapy methods for epilepsy (ketogenic diet, vagus nerve stimulation) in this group of patients are covered. To conclude the article, some considerations on the prognosis for different clinical variants of non-ketotic hyperglycinemia in pediatric patients are provided.